Integrated 99mTc-PYP Scintigraphy, 18F-FDG PET/CT, and Cardiac Magnetic Resonance in Suspected Infiltrative and Inflammatory Cardiomyopathy: Initial Experience - Akhter, Afroza; Biswas, Shankar Kumar; Islam, A K M Monwarul; Sharmin, Shaila; Rahman, Farhana; Afrin, Rawnak; Hossain, Sadia; Islam, Sabrina; Alam, Sumaiya; Hasan, Tanvirul; et al. (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Cardiac amyloidosis (CA) and cardiac sarcoidosis (CS) are underrecognized causes of cardiomyopathy and may phenotypically overlap with hypertrophic cardiomyopathy (HCM). Accurate differentiation among infiltrative, inflammatory, and phenotypically similar cardiomyopathies is clinically important because treatment and prognosis differ substantially. Objective: To assess the role of a multimodality imaging approach using 99mTc-pyrophosphate (PYP) scintigraphy, 18F-FDG PET/CT, and cardiac magnetic resonance (CMR) in patients with infiltrative or inflammatory cardiomyopathy. Patients & methods: This prospective observational study enrolled 25 consecutive patients (aged 19–80 years; 48% male) who were referred for nuclear imaging evaluation of suspected infiltrative or inflammatory cardiomyopathy between August 2023 and December 2025. All patients underwent electrocardiography, echocardiography, nuclear imaging, and laboratory evaluation. CMR was performed in 15 patients, while 10 did not undergo CMR. 99mTc-PYP scintigraphy was used to assess transthyretin cardiac amyloidosis (ATTR-CM), and 18F-FDG PET/CT with dietary suppression was performed to evaluate myocardial inflammation. No patient underwent endomyocardial biopsy. Results: Non-invasive etiologic classification was achieved in 17 of 25 patients (68.0%): CA in 4 (16.0%), CS in 8 (32.0%), and HCM in 5 (20.0%); 8 patients (32.0%) remained indeterminate. All CA cases demonstrated grade 2–3 myocardial uptake on PYP scintigraphy in the absence of monoclonal protein on serum immunofixation electrophoresis. Among CS cases, FDG PET/CT showed focal, focal-on-diffuse or heterogenous myocardial uptake in 5 of 8 patients, with extracardiac pulmonary involvement in 2. Conclusion: Multimodality imaging with PYP scintigraphy, FDG PET/CT, and CMR may improve etiologic classification and diagnostic confidence in patients with suspected infiltrative and inflammatory cardiomyopathy, particularly in settings where biopsy and genetic testing are not routinely available. Bangladesh J. Nuclear Med. 29(1): 19-27, 2026